Chemical Functionalization of Nanodiamonds: Opportunities and Challenges Ahead. (27th August 2019) - Reina, Giacomo; Zhao, Li; Bianco, Alberto; Komatsu, Naoki
Abstract: Nanodiamond(ND)‐based technologies are flourishing in a wide variety of fields spanning from electronics and optics to biomedicine. NDs are considered a family of nanomaterials with an sp 3 carbon core and a variety of sizes, shapes, and surfaces. They show interesting physicochemical properties such as hardness, stiffness, and chemical stability. Additionally, they can undergo ad‐hoc core and surface functionalization, which tailors them for the desired applications. Noteworthy, the properties of NDs and their surface chemistry are highly dependent on the synthetic method used to prepare them. In this Minireview, we describe the preparation of NDs from the materials‐chemistry viewpoint. The different methodologies of synthesis, purification, and surface functionalization as well as biomedical applications are critically discussed. New synthetic approaches as well as limits and obstacles of NDs are presented and analyzed. Abstract : Nanodiamanten (NDs) werden in einer Vielzahl von Bereichen eingesetzt, von der Elektronik und Optik bis zur Biomedizin. Kontrollierte Oberflächenfunktionalisierung kann NDs in Hochleistungsnanomaterialien überführen. In diesem Kurzaufsatz werden verschiedene Methoden der Synthese, Reinigung und Oberflächenfunktionalisierung sowie biomedizinische Anwendungen kritisch diskutiert.